Strongly Lipschitz up-Nuclear Operators - Belacel Amar; Bey Khedidja (Moroccan Journal of Pure and Applied Analysis, 2019)
In this paper, we introduce the notion of strongly Lipschitz up-nuclear operators. Among other results, we prove an analog of the factorization theorem for these classes and characterize their conjugates.